2019
DOI: 10.1089/cyber.2018.0624
|View full text |Cite
|
Sign up to set email alerts
|

The CSS-12: Development and Validation of a Short-Form Version of the Cyberchondria Severity Scale

Abstract: Cyberchondria is defined as an increase in anxiety about one's health status as a result of excessive online searches. McElroy and Shevlin (2014) developed the first multidimensional, self-report measure of this construct-the Cyberchondria Severity Scale (CSS). The CSS consists of 33 items which can be summed to form a total score, and/or 5 subscale scores. The aim of the present study was to develop a short-formversion of the CSS, removing the 'Mistrust' subscale. Participants were undergraduate students from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 41 publications
7
103
0
Order By: Relevance
“…An example item is "If I notice an unexplained bodily sensation, I will search for it on the internet." The CSS-12 scale demonstrated reliable internal consistency as stated by the authors, with higher scores indicating increased levels of awareness [13]. Permission to use the survey was obtained from the owner of the instrument prior to the data collection.…”
Section: The Short-form Version Of the Cyberchondria Severity Scalementioning
confidence: 53%
See 1 more Smart Citation
“…An example item is "If I notice an unexplained bodily sensation, I will search for it on the internet." The CSS-12 scale demonstrated reliable internal consistency as stated by the authors, with higher scores indicating increased levels of awareness [13]. Permission to use the survey was obtained from the owner of the instrument prior to the data collection.…”
Section: The Short-form Version Of the Cyberchondria Severity Scalementioning
confidence: 53%
“…The CSS-12 is a brief, reliable, and valid tool to measure worry/anxiety attributable to excessive online health search [13]. The scale consists of 12 items that are rated on a 5-point Likert-scale ranging from 1 ("never") to 5 ("always").…”
Section: The Short-form Version Of the Cyberchondria Severity Scalementioning
confidence: 99%
“…The German short version of the Cyberchondria Severity Scale (CSS-15; Barke, Bleichhardt, Rief, & Doering, 2016;McElroy & Shevlin, 2014) uses 15 items to assess five dimensions of cyberchondria: "compulsion" (interruption of everyday activities due to health-related Internet research), "distress" due to Internet research, "excessiveness", "seeking reassurance", and "mistrust of medical professionals". In previous studies, the subscale "mistrust" tended to be a separate construct, so that this subscale was excluded in the present study as well as in previous studies (Fergus, 2014;McElroy et al, 2019;Norr, Allan, Boffa, Raines, & Schmidt, 2015). This version with four subscales is also equivalent to the English short version with 12 items (CSS-12;McElroy et al, 2019).…”
Section: Cyberchondria Related To the Covid-19 Pandemic (Cyberchondrimentioning
confidence: 92%
“…In previous studies, the subscale "mistrust" tended to be a separate construct, so that this subscale was excluded in the present study as well as in previous studies (Fergus, 2014;McElroy et al, 2019;Norr, Allan, Boffa, Raines, & Schmidt, 2015). This version with four subscales is also equivalent to the English short version with 12 items (CSS-12;McElroy et al, 2019). For the current study, the items have been slightly modified so that the Internet research refers to the COVID-19 pandemic (e.g., "I panic when I read online that a symptom I have might be related to the coronavirus pandemic").…”
Section: Cyberchondria Related To the Covid-19 Pandemic (Cyberchondrimentioning
confidence: 94%
“…The concept of cyberchondria was developed on the basis of its hypothesized relationships with health anxiety and hypochondriasis. Many studies [11,12,14,[17][18][19][20][21][22][23][24][25][26] have confirmed moderate to strong correlations between cyberchondria and health anxiety (rs ranging from 0.48 to 0.68, depending on the instrument used for the assessment of health anxiety). Only one study [13] found this correlation to be relatively weak (r = 0.23).…”
Section: Relationships Between Cyberchondria and Other Constructsmentioning
confidence: 99%